Bronchopleural Fistula as a Complication in a COVID-19 Patient Managed With Endobronchial Valves - Andrew Talon MD; Muhammad Zohab Arif MD; Hesham Mohamed MD; Abid Khokar MD; Ali Imran Saeed MD (SAGE Publishing, 2021)
Bronchopleural fistula (BPF) is associated with high morbidity if left untreated. Although rare, the frequency of BPF in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is becoming recognized in medical literature. We present a case of a 64-year-old male with BPF with persistent air leak due to SARS-CoV-2 pneumonia treated with Spiration Valve System endobronchial valve (EBV). An EBV was placed in the right middle lobe with successful cessation of air leak. In conclusion, the use of EBVs for BPF with persistent air leaks in SARS-CoV-2 patients who are poor surgical candidates is effective and safe.